Low-Cost Online Monitoring System for the Etching Process in Fiber Optic Sensors by Computer Vision - Wenceslao Eduardo Rodríguez-Rodríguez; Jesús Abraham Puente-Sujo; Adolfo Josué Rodríguez-Rodríguez; Ignacio R. Matias; David Tomás Vargas-Requena; Luis Antonio García-Garza (Sensors, 2023)
The present research exposes a novel methodology to manufacture fiber optic sensors following the etching process by Hydrofluoric Acid deposition through a real-time monitoring diameter measurement by computer vision. This is based on virtual instrumentation developed with the National Instruments® technology and a conventional digital microscope. Here, the system has been tested proving its feasibility by the SMS structure diameter reduction from its original diameter of 125 <semantics>μ</semantics> until approximately 42.5<semantics> μm</semantics>. The results obtained have allowed us to demonstrate a stable state behavior of the developed system during the etching process through diameter measurement at three different structure sections. Therefore, this proposal will contribute to the etched fiber optic sensor development that requires reaching an enhanced sensitivity. Finally, to demonstrate the previously mentioned SMS without chemical corrosion, and the etched manufactured SMS, both have been applied as glucose concentration sensors.